Highly enhanced dielectric loss of MgO-doped Ba0.67Sr0.33TiO3 ceramics prepared by a non-contamination DCC-HVCI method. Issue 14 (November 2019) - Lou, Chen-Hua; Chen, An-Nan; Lu, Lu; Wu, Jia-Min; Cheng, Li-Jin; Liu, Rong-Zhen; Chen, Shuang; Chen, Ying; Shi, Yu-Sheng; Li, Chen-Hui
Abstract: MgO-doped Ba0.67 Sr0.33 TiO3 (BST) ceramics with uniform microstructure and enhanced dielectric loss were prepared by direct coagulation casting via high valence counter ions (DCC-HVCI) method. MgO was utilized as acceptor dopant as well as coagulating agent to release Mg 2+ solidifying ceramic suspensions. Effect of sintering temperature and MgO doping content on microstructure and dielectric properties of BST ceramics was investigated. It was found that the loss tangent value (tan δ) decreased remarkably from 0.025 to 0.004 with increasing MgO concentration from 0.5 to 1.5 mol%. The 1.5 mol% MgO-doped BST ceramics processed high density of 99.5% and tan δ of 0.004 which is improved by 150% compared with that of dry-pressed samples. This improvement can be attributed to the ubiquitous distribution of MgO in BST ceramic matrix leading to the enhanced inhibitive effect. This paper provides a novel facial route to prepare high-performance functional ceramics with high reliability and low cost.